EFISIENSI WAKTU PERSIAPAN SET-UP PADA MESIN FILLING BULK GEL DENGAN METODE SMED DI PT XYZ - Fairuz Majid; Tasya Mursalina; Rifatul Ngatiqoh; Muchammad Fauzi (LPPM Universitas Bina Bangsa, 2022)
PT XYZ is a company engaged in the pharmaceutical and cosmetic sector. The line used is a shared facility between drug and cosmetic production. This type of product is in the form of cream, gel and semi solid. These bulk filling machines are used interchangeably, several problems were encountered, namely the length of the preparation process for the filling machine setup, causing delays in the filling process. PT XYZ made the right improvement by reducing the setup time for the filling machine preparation using the SMED (Single Minute Exchange of Dies method) method. SMED on filling machines is done by dividing a series of jobs in two stages of filling preparation process with external settings and the second stage of filling machine setup process. The results of the efficiency of the preparation time and machine set up can reduce the time by 40%